Free and Easy - Sedgwick, Edward; Smith, Leonard; Keaton, Buster; Page, Anita; Montgomery, Robert (Warner Archive Collection, 2014)
In his first sound film, Buster Keaton plays the inept manager of beauty contest winner Anita Page, whom he takes (along with her mother, Trixie Friganza) to Hollywood to become a star. After Keaton crashes the gate at MGM, it is he who is "discovered" and ends up in front of the cameras. Luckily, Page falls in love with Robert Montgomery, so her trip to California isn't a total washout. Although anything but an outstanding Keaton vehicle, "Free and Easy" provides a fascinating look at the MGM studio system circa 1930. The film also features cameo appearances by Jackie Coogan, Lionel Barrymore, and Cecil B. DeMille. [www.tvguide.com]